Demography, human development and economic conditions - Buisson, Marie-Charlotte; Wardak, A.; Jan, I. (CAB International, 2023)
The Kabul, Kurram, and Gomal river basins are home to approximately 43 million (authors’ own calculation) people who experience a diverse set of human and economic development realities. This chapter draws profiles of the basins in terms of demography and human and economic development. In doing so, the authors illustrate the human realities that overlie the hydrological units. This chapter presents basin-level data by combining and rescaling data for specific administrative units in Afghanistan and Pakistan. The authors find disparities between and within the two countries in terms of population size, migration dynamics, economic indicators and production of power. Despite these differences, people share similar challenges in achieving food security, poverty alleviation, and mitigation and adaptation to climate change. Improved, co-ordinated strategies and policies have the potential to strengthen the governance of these transboundary river basins and deliver better outcomes for people and resource sustainability.